2015
DOI: 10.1007/s00253-015-7224-7
|View full text |Cite
|
Sign up to set email alerts
|

Replacing a piece of loop-structure in the substrate-binding groove of Aspergillus usamii β-mannanase, AuMan5A, to improve its enzymatic properties by rational design

Abstract: To perfect the enzymatic properties of AuMan5A, a mesophilic glycoside hydrolase (GH) family 5 β-mannanase from Aspergillus usamii, its loop-structure substitution was carried out by rational design and followed by megaprimer PCR. Based on the structural analysis and enzymatic property comparison of various β-mannanases, a piece of loop-structure with seven amino acids between two β-strands (βD and βE) in the substrate-binding groove, named "Loop DE," was speculated to be correlative to the thermostability and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
2
8
0
1
Order By: Relevance
“…However, substituting S199 by the most flexible amino acid residue G could facilitate the flexibility of 187–198 loop. Improving the flexibility of the catalytic core is a widely adopted strategy for enhancing the catalytic activity of the enzyme (Huang et al ., 2014; Dong et al ., 2016; Zheng et al., 2018). P191 M, P194E and S199G could directly or indirectly increase the flexibility of the catalytic core of enzyme, thus presumably facilitating the reaction at the catalytic residue E190.…”
Section: Resultsmentioning
confidence: 99%
“…However, substituting S199 by the most flexible amino acid residue G could facilitate the flexibility of 187–198 loop. Improving the flexibility of the catalytic core is a widely adopted strategy for enhancing the catalytic activity of the enzyme (Huang et al ., 2014; Dong et al ., 2016; Zheng et al., 2018). P191 M, P194E and S199G could directly or indirectly increase the flexibility of the catalytic core of enzyme, thus presumably facilitating the reaction at the catalytic residue E190.…”
Section: Resultsmentioning
confidence: 99%
“…The protein/enzyme with high T m meant it has a high thermostability ( Jang et al 2010). The T m of xylanase here was measured by protein thermal shift (PTS) method (Dong et al 2016), using a PTS Kit (Applied Biosystems, Carlsbad, CA, USA) and a LightCycler 480II 96 Real-Time PCR system (Roche, Basel, Switzerland). Three replicates were conducted independently.…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that the alteration of the loop structures in proximity to the active centers of the glycoside hydrolyzes may enhance their catalytic efficiency and/or thermostability. Dong et al (2016) have sought to improve the characteristics of an Aspergillus usamii derived β-mannanase (AuMan5A) by substitution of its loop structure. Based on enzymatic characteristics and structural analysis of various GH 5 β-mannanases, three mutants (AuMan5A, AuMAN5A-An, AuMAN5A-AF) are designed by substituting a piece of loop structure with seven amino acids in the substrate binding groove of AuMan5A with the corresponding sequences of three other family 5 β-mannanases, respectively.…”
Section: Enhancing Thermostability Of β-Mannanasesmentioning
confidence: 99%